Correction: A new strategy for the controllable growth of MOF@PBA architectures. Issue 27 (2nd July 2020) - Xiao, Xiao; Zhang, Guangxun; Xu, Yuxia; Zhang, Hualin; Guo, Xiaotian; Liu, Yong; Pang, Huan
Abstract : Correction for 'A new strategy for the controllable growth of MOF@PBA architectures' by Xiao Xiao et al., J. Mater. Chem. A, 2019, 7, 17266–17271, DOI: ; 10.1039/C9TA05409J .